Seeing is believing: Neural mechanisms of action–perception are biased by team membership. Issue 9 (30th January 2012) - Molenberghs, Pascal; Halász, Veronika; Mattingley, Jason B.; Vanman, Eric J.; Cunnington, Ross
<x xml:space="preserve">Abstract</x> Group identification can lead to a biased view of the world in favor of "in‐group" members. Studying the brain processes that underlie such in‐group biases is important for a wider understanding of the potential influence of social factors on basic perceptual processes. In this study, we used functional magnetic resonance imaging (fMRI) to investigate how people perceive the actions of in‐group and out‐group members, and how their biased view in favor of own team members manifests itself in the brain. We divided participants into two teams and had them judge the relative speeds of hand actions performed by an in‐group and an out‐group member in a competitive situation. Participants judged hand actions performed by in‐group members as being faster than those of out‐group members, even when the two actions were performed at physically identical speeds. In an additional fMRI experiment, we showed that, contrary to common belief, such skewed impressions arise from a subtle bias in perception and associated brain activity rather than decision‐making processes, and that this bias develops rapidly and involuntarily as a consequence of group affiliation. Our findings suggest that the neural mechanisms that underlie human perception are shaped by social context. Hum Brain Mapp 34:2055–2068, 2013. © 2012 Wiley Periodicals, Inc.